Effect of a Novel Alpha/Beta Hydrolase Domain Protein on Tolerance of K. marxianus to Lignocellulosic Biomass Derived Inhibitors - Wu, Dan; Wang, Dongmei; Hong, Jiong (Frontiers in Bioengineering and Biotechnology, 2020)
The multiple inhibitors tolerance of microorganism is important in bioconversion of lignocellulosic biomass which is a promising renewable and sustainable source for biofuels and other chemicals. The disruption of an unknown α/β hydrolase, which was termed KmYME and located in mitochondria in this study, resulted in the yeast more susceptible to lignocellulose-derived inhibitors, particularly to acetic acid, furfural and 5-HMF. The KmYME disrupted strain lost more mitochondrial membrane potential, showed increased plasma membrane permeability, severer redox ratio imbalance, and increased ROS accumulation, compared with those of the non-disrupted strain in the presence of the same inhibitors. The intracellular concentration of ATP, NAD and NADP in the KmYME disrupted strain was decreased. However, disruption of KmYME did not result in a significant change of gene expression at the transcriptional level. The KmYME possessed esterase/thioesterase activity which was necessary for the resistance to inhibitors. In addition, KmYME was also required for the resistance to other stresses including ethanol, temperature, and osmotic pressure. Disruption of two possible homologous genes in S. cerevisiae also reduced its tolerance to inhibitors.